Unlocking ESG Value in Crisis: A Corporate Life Cycle Perspective from Indonesia’s Pandemic Experience - Poespawijaya, Natalia; Mudjilah, Rahayu; Krismiaji, Krismiaji (Profit: Jurnal Adminsitrasi Bisnis, 2026)
This study examines how ESG disclosure, funding policy, and corporate life cycle influence firm value, and whether ESG plays a moderating role in these relationships. Using panel data from 149 non-financial firms listed on the Indonesia Stock Exchange from 2021 to 2024, the analysis employs a Fixed Effects Model to control for unobserved firm characteristics. The results show that ESG disclosure, funding policy, and life cycle stage do not have a significant direct impact on firm value. However, ESG significantly moderates the relationship between funding policy and firm value. In practice, this means that when firms adopt prudent leverage, strong ESG performance helps strengthen investor confidence by providing an additional signal of credibility and responsible financial management. In contrast, ESG does not moderate the corporate life cycle–firm value relationship, suggesting that sustainability practices in Indonesia are not yet differentiated across development stages. A robustness check further shows that ESG’s influence weakens during the pandemic years, when firms prioritize liquidity and operational survival, but begins to regain relevance in the post-pandemic period. Overall, the findings imply that ESG contributes to firm value not as a standalone factor, but through its interaction with financing decisions.